The Opposing Roles of IVS2+691 CC Genotype and AC/AG Diplotype of 118A>G and IVS2+691G>C of OPRM1 Polymorphisms in Cold Pain Tolerance Among Opioid-Dependent Malay Males on Methadone Therapy. Issue 2 (December 2015) - Zahari, Zalina; Lee, Chee; Ibrahim, Muslih; Musa, Nurfadhlina; Yasin, Mohd; Lee, Yeong; Tan, Soo; Mohamad, Nasir; Ismail, Rusli
Abstract Introduction We recently reported that a majority of opioid-dependent Malay males on methadone therapy are cold pain sensitive. It is postulated that commonOPRM1 polymorphisms may be responsible. This study investigated the association between 118A>G (dbSNP rs1799971) and IVS2+691G>C (dbSNP rs2075572) variants on cold pain responses among opioid-dependent Malay males on methadone maintenance therapy. Methods Cold pain responses including pain threshold, pain tolerance, and pain intensity were measured using the cold pressor test. DNA was extracted from the venous blood before polymerase chain reaction genotyping. Repeated measures analysis of variance was used to compare the cold pain responses andOPRM1 polymorphisms (118A>G and IVS2+691G>C) using models including genotype dominant and recessive models, allelic additive models, and analysis of haplotypes and diplotypes. Results A total of 148 participants were recruited. With the recessive model, those with IVS2+691 homozygous CC genotype had a shorter cold pain tolerance time than those without CC genotype (i.e., GG/GC genotype; 29.81 vs. 43.08 s, respectively, P  = 0.048). On the other hand, with diplotype analysis, participants with combined homozygous 118 AA genotype and heterozygous IVS2+691 GC genotype (i.e., AC/AG diplotype) had a longer cold pain tolerance time than those without this diplotype (49.34 vs. 31.48 s, respectively, P  = 0.043). Cold pain threshold was not associated with any of the 118A>G and IVS2+691G>C variations despite being analyzed using various models (allP  > 0.05). Conclusion The IVS2+691 CC genotype and AC/AG diplotype of 118A>G and IVS2+691G>C seem to have opposing roles in pain tolerance among opioid-dependent Malay males on methadone therapy. Haplotypes ofOPRM1 may be associated with altered binding affinity.